The political-pedagogical projects of heritage education: An analysis of heritage education proposals present in UNESCO's international documents - Gonçalves, Ana Carolina Fernandes; de Mari , Cezar Luiz (Seven Editora, 2024)
This text is a product of the research carried out for the Master's Degree in Education, whose object is the pedagogical political project presented by UNESCO for heritage education, through the initiatives encouraged by it for the preservation of cultural and natural heritage. From a qualitative research of documentary analysis of UNESCO's recommendations, declarations and conventions, it was possible to reconstruct the proposals and political uses of heritage education and political-pedagogical projects planned by this agency. The result presented is an overview of the pedagogical policy designed for heritage preservation and its economic exploitation, whether as a support for the creation of sustainable networks for traditional communities, responsible exploitation of cultural tourism by public and private agents, and scientific and pedagogical responsibility in the preservation of material and immaterial cultural assets. The contribution of this text is, in the end, a reflection on the importance of establishing criteria to evaluate the impacts of these political pedagogical projects on the public it targets. DOI:https://doi.org/10.56238/sevened2024.018-056